Taraftarların çevrimiçi alışverişe karşı tutumlarının incelenmesi: süper lig futbol kulüp taraftarları üzerine bir araştırma - Akyüz, Oktay (My University, 2017)
Taraftarların Çevrimiçi Alışverişe Karşı Tutumlarının İncelenmesi: Süper Lig Futbol Kulüp Taraftarları Üzerine Bir Araştırma Amaç Spor Toto Süper Ligi futbol takımı taraftarlarının, kulüplerinin internet sitesi üzerinden çevrimiçi alışverişe karşı tutumlarının belirlenmesi ve taraftarların demografik özelliklerine göre tutumları arasındaki farkın incelenmesidir. Gereç ve Yöntem Taraftarlara, kişisel bilgi formu ve tutum ölçeği, internet üzerinden e-anket yoluyla uygulanmıştır. Çalışmaya kulüplerinin internet sitesi üzerinden çevrimiçi alışveriş yapan 478 (382 Erkek, 96 Kadın) ve yapmayan 290 (170 Erkek,120 Kadın) olmak üzere toplam 768 Spor Toto Süper Ligi futbol takımı taraftarları katılmıştır. Bulgular ve Sonuçlar Yapılan analizler sonucunda, taraftarlarının kulüplerinin internet sitesi üzerinden çevrimiçi alışverişe karşı tutumları ile sosyo demografik özellikleri, tutumların alt bileşenleri olan bilişsel, duygusal ve davranışsal tutum puanı ile toplam tutum puanı çerçevesinde ayrı ayrı incelendiğinde; cinsiyete göre kadınların davranışsal tutum puanı erkeklerden yüksek, yaşa göre bilişsel, duygusal, davranışsal ve toplam tutum puanı 46 yaş ve üzeri taraftarların puan ortalaması diğer yaş grupları puan ortalamasına göre yüksek, Eğitim ve Gelir durumuna göre davranışsal tutumda yüksek, tutulan takımlara göre davranışsal tutum ve toplam tutum puanı yüksek çıkarken medeni durum ve yaşanılan şehre göre anlamlı bir farklılık gözlenmemiştir. evrimiçi Alışveriş, Spor Kulüplerinde Çevrimiçi (Online) Alışveriş, Taraftar, Taraftar Davranışları, Taraftar Tutumları.

Examination of the Attitudes of Supporters' About the Online Shopping Through Websites: A Research on the Supporters of Spor Toto Super League Football Purpose: To determine the attitudes of Spor Toto Super League football clubs' supporters about the online shopping through websites and analysing the differences among the manners according to demographic characteristics of the supporters. Instruments and Methodology: Personal information form and attitude scale have been implied to supporters by online e-survey. Material and Method in total 768 people who compose of 485 people (382 male, 96 female) who make online shopping and 290 people (170 male, 120 female) who do not make online shopping through clubs’ websites have participated the inquiry. Findings and Results: As a result of the implied analysis, as the attitude of supporters about the online shopping through websites and their socio-demographic characteristics are separately examined in the scope of the sub components of attitudes as cognitive, sentimental and behavioural attitude scores and the total attitude score, the observations are as follows: attitude score with regard to gender is higher by females than males; sensual, the average of 46 years and older supporters is higher than the average of the other age groups' behavioural and total attitude score with regard to age; behavioural attitude is high with regard Educational and income status; behavioural attitude and total score is high with regard to supported club while there is no significant difference with regard to marital status and the city of residence. Key Words: Online Shopping, E-Commerce in Sports Clubs, Fan, Fan Behavior, Fan Attitudes.
Keywords: Futbol taraftarları; Türkiye